Meaning in linguistic interaction : semantics, metasemantics, philosophy of language - Jaszczolt, Katarzyna (b)
This book offers a semantic and metasemantic inquiry into the representation of meaning in linguistic interaction. The author's view represents the most radical stance on meaning to be found in the contextualist tradition and thereby the most radical take on the semantics/pragmatics boundary. It allows for the selection of the cognitively plausible object of inquiry without being constrained by such distinctions as what is said/what is implicated or what is linguistic and what is extralinguistic. She argues that this is the only promising stance on meaning. The analysis transcends the traditional distinctions drawn, and traditional questions posed, in post-Gricean pragmatics and philosophy of language. It heavily relies on the dynamic construction of meaning in discourse, using truth conditions as a tool but at the same time conforming to pragmatic compositionality - whereby aspects of meaning that enter this composition have very different provenance.
Includes bibliographical references (p. 193 - 215) and index.
Keywords: Language and languages -- Philosophy; Semantics